Pendidikan Dan Pengentasan Kemiskinan Dalam Pembangunan Berkelanjutan (SDGs) - Aan Zulyanto (Universitas Bengkulu, 2022)
The aim of the research is to provide an overview of how education and expenditure on education functions can alleviate poverty as an effort to achieve sustainable development goals (SDGs). The method used is documentation with sources of information derived from previous research articles. Result show that Educational capacity building and poverty alleviation are still the main goals of sustainable development/SDGs. In several countries, especially poor countries, the achievement of educational capacity to achieve the MDGs has not been achieved and is the main agenda in the SDGs. Keywords: Education, Poverty, Sustainable Development Goals